1998
DOI: 10.1136/gut.42.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s-like reaction in diverticular disease

Abstract: (Gut 1998;42:392-395)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(54 citation statements)
references
References 13 publications
2
51
0
1
Order By: Relevance
“…This is consistent with an M. avium subsp. paratuberculosis superinfection in a preexisting abnormality and is in line with the previous description of typical changes associated with CD affecting a segment of colon with diverticulitis (13). A fifth patient diagnosed with lymphocytic colitis had extensive intraepithelial lymphocytosis throughout the colon.…”
Section: Discussionsupporting
confidence: 68%
“…This is consistent with an M. avium subsp. paratuberculosis superinfection in a preexisting abnormality and is in line with the previous description of typical changes associated with CD affecting a segment of colon with diverticulitis (13). A fifth patient diagnosed with lymphocytic colitis had extensive intraepithelial lymphocytosis throughout the colon.…”
Section: Discussionsupporting
confidence: 68%
“…Both CD and JID are seen with sufficient frequency that unless one disease protects from the other, one would occasionally expect to see coincident disease (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…However, some other studies indicated that some patients with SCADD may progress to clinically subsequent ‘classic’ Crohn’s disease. Gledhill and Dixon [22 ]and Burroughs et al [26 ]both reported 17 cases of diverticular colitis with Crohn’s-like features. Those have been followed and only 2 cases subsequently developed Crohn’s disease.…”
Section: Diverticular Colitismentioning
confidence: 99%
“…Gledhill and Dixon [22] reported 11 cases of Crohn’s disease-type diverticulitis with typical ‘classic’ histological features of Crohn’s disease-like transmural inflammation, granulomas and ulceration. In 9 patients, the features were confined to the resected specimens only and none of these patients progressed to full-blown Crohn’s disease.…”
Section: Diverticular Colitismentioning
confidence: 99%